Four essays on the effects of Information and Communication Technologies (ICTs) on structural transformation in Sub-Saharan Africa (SSA) - (:unkn) unknown (My University, 2022)
Structural transformation remains a necessity for sub-Saharan African (SSA) economies to improve people's living conditions and halt poverty and inequality. While the economic literature has proposed several channels to achieve this, these have generally had unsatisfactory results. Thus, this study, following many authors, has as its main objective to establish ICTs as new channels for structural transformation. In order to achieve this main objective, a theoretical review of the literature is first carried out; it allows us to pose the problem of structural transformation in terms of productivity and competitiveness, but also to decompose productivity into its intra-industry and inter-industry components and to decompose competitiveness into its price and non-price aspects.In a second step, an empirical analysis allows us to assess the effects of ICT first on intra-industry productivity and inter-industry productivity, and then on price and non-price competitiveness in SSA. To assess the effects of ICT on intra-industry and inter-industry productivity, we use World Bank Enterprise Survey data, the Fabricant’s decomposition method and generalized least squares. To assess the effects of ICT on price and non-price competitiveness, we use data from the World Development Indicators (WDI), the Atlas of Economic Complexity (ACE) and UNCTAD. As methods of analysis, we use a vector autoregression (VAR) panel model for price competitiveness and the generalized method of moments (GMM) panel system for non-price competitiveness. The main results show that high internet usage has overall positive effects on productivity in all industries in SSA economies, on intra-industry and inter-industry productivity, and on price and non-price competitiveness in SSA. Our main recommendation is that SSA countries facilitate and encourage the integration of ICTs in all sectors of activity, encourage the use of the complex and sophisticated functions of the internet and promot
Keywords: African Research